Letter from Frank H. Westheimer to Theodore Benfey - Westheimer, Frank H. (1971)
Westheimer expresses gratitude for being included in the dedication of a book authored by Benfey.
Keywords: Benfey, Theodor, 1809-1881; Westheimer, Frank H.; Hammett, Louis P. (Louis Plack), 1894-1987; Ingold, Christopher